2016
DOI: 10.1111/eth.12517
|View full text |Cite
|
Sign up to set email alerts
|

Cautious Crows: Neophobia in Torresian Crows (Corvus orru) Compared with Three Other Corvoids in Suburban Australia

Abstract: Corvids (Family: CORVIDAE) are a clade of some 120 species widespread throughout much of the world that have attracted the interest of researchers due to their impressive cognitive abilities. The group is, however, also generally described as neophobic, a trait that increases the difficulty of undertaking such research. In Australia, Torresian crows (Corvus orru) have, like corvid species worldwide, thrived in urban environments, sharing this habitat with a number of other corvoid (Superfamily: CORVOIDEA) spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 44 publications
(116 reference statements)
0
37
0
Order By: Relevance
“…Species comparisons provide opportunities to examine the variability of behavioural responses at the level of a species 4 . Comparative studies of variability in individual's behavioural responses across species are limited 33,34,[64][65][66][67][68][69] , even though this approach is necessary to identify potential factors contributing to individual-level variability of behavioural responses among closely-related species. Previous comparative studies that focused on identifying factors influencing exploratory behaviour at a species level have identified three main factors: the www.nature.com/scientificreports www.nature.com/scientificreports/ relative sociality of the species (e.g., Social Niche Hypothesis 70,71 ), the foraging ecology and habitat complexity of the species 10,33,34,72 , and the migratory patterns of the species 67,73 .…”
Section: Discussionmentioning
confidence: 99%
“…Species comparisons provide opportunities to examine the variability of behavioural responses at the level of a species 4 . Comparative studies of variability in individual's behavioural responses across species are limited 33,34,[64][65][66][67][68][69] , even though this approach is necessary to identify potential factors contributing to individual-level variability of behavioural responses among closely-related species. Previous comparative studies that focused on identifying factors influencing exploratory behaviour at a species level have identified three main factors: the www.nature.com/scientificreports www.nature.com/scientificreports/ relative sociality of the species (e.g., Social Niche Hypothesis 70,71 ), the foraging ecology and habitat complexity of the species 10,33,34,72 , and the migratory patterns of the species 67,73 .…”
Section: Discussionmentioning
confidence: 99%
“…Corvids have become among the most abundant avian taxa found in urban environments throughout the world (Marzluff et al 2001). This abundance is despite millennia of active persecution and antipathy in both rural and urban areas (Knight 1984) and, unlike many other urban exploiters (Blair 1996), innate behavioural characteristics that include neophobia and a persistent lack of habituation (Brown & Jones 2016). Nonetheless, urbanised corvids can demonstrate clear evidence of tolerance of human presence; Vines & Lill (2015) showed that Little Ravens in urban Melbourne allowed humans to approach far closer than conspecifics in exurban areas.…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable range of foods consumed by urban Torresian Crows demonstrates clearly a highly versatile diet and a willingness to try thoroughly unfamiliar items. Although Brown & Jones (2016) recently found this species to be strongly neophobic, being reluctant to approach a familiar food item when a novel object was nearby, it appears that this characteristic is overcome with time. For example, the various forms of packaging (foil, paper bags, packets etc.)…”
Section: 2mentioning
confidence: 96%
See 2 more Smart Citations